Yaw Systems for wind turbines : Overview of concepts, current challenges and design methods - Manuel Moo-Gyn Kim and Peter Dalhoff (Journal of physics, 2014)
Looking at the upscaling of the rotor diameter not only the loss in power production but the aerodynamic loads arising from yaw misalignment will have an increasing impact on the yaw system design in future wind turbines. This paper presents an overview of yaw systems used in current wind turbines and a review of patents with regards to the yaw system. The current state of the art of yaw systems has been analyzed through a systematic literature review. Further a patent analysis has been done through the European Patent Office. Todays design and strength requirements as per IEC and GL standards will be reviewed and alternative design calculations will be discussed. Over 100 patents have been identified as relevant to the yaw system and have been analyzed. It has been found that most patents are dealing with load reduction possibilities on the yaw system, where fatigue loads seem more of a problem than ultimate loads. Most of these patents concern especially the yaw actuator, which consists of multiple electrical motors, reduction gears and shaft pinions. This is due to the nature of the gearing in the actuator and the gearing between the shaft pinion and the ring gear. This coincides with the patents for yaw brakes, which mostly aim to reduce the fatigue loads during yaw maneuverer and during nacelle standstill. Patents for the yaw bearing are incorporating the reduction of loads through the usage of friction bearings or different bearing arrangement approaches. The paper shows that the conventional yaw system designs are still trying to meet the high requirements regarding the lifetime of a wind turbine and turbulent wind loads. New designs for yaw systems in general are hard to find. Many patents concentrate on control algorithms that depend on additional instruments and incorporate electromechanical systems.